Dança no desenvolvimento de pessoas com transtorno do espectro autista - Lima, Beatriz dos Santos Alvarez de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In the last decades, the index of diagnoses of people with Autism Spectrum Disorder (ASD) has been growing significantly all over the world, however, its wide complexity makes it a disorder still far from being fully understood. Currently, the resources used to treat and monitor people with ASD include several types of therapy, including dance. This study aimed to investigate the teachers' perception of dance teaching for people diagnosed with ASD. And as specific objectives: to identify if there are benefits of the experience of dance for people diagnosed with ASD and to raise if the teaching of dance for people with ASD affects the lives of teachers. Following a qualitative approach, data were collected through interviews with a script of semi-structured questions, addressed to professionals who worked in dance teaching for people with ASD. In view of the analysis of the responses, we identified three thematic categories: Practice vs. Theory; The individual as a unique being and The observed answers. It was possible to identify that the experiences with this public are very unique, since each professional has a different experience due to the specificities of their students; there is a need to understand the student as a unique and singular individual and respect their specificities; there was improvement in communication, reduction of stereotyped movements, improvement of affection and demonstration of affection, socialization and motor performance. It was concluded with the research that dance provides benefits in different spheres of the Spectrum, confirming the efficiency of this intervention in the treatment of the individual, but, in addition, reinforcing the importance of a well-built teacher/student relationship, based on respect, listening and care, so that there is room for these benefits to develop in due time and in the right way.

Nas últimas décadas, o índice de diagnósticos de pessoas com Transtorno do Espectro Autista (TEA) vem crescendo significativamente em todo o mundo, porém, sua ampla complexidade o torna um transtorno ainda distante de ser compreendido totalmente. Atualmente, as possibilidades de intervenção para desenvolvimento da pessoa com TEA, incluem diversos tipos de terapia, dentre elas a dança. Este trabalho teve como objetivo geral investigar qual a percepção de professoras sobre o ensino da dança para pessoas diagnosticadas com TEA. E como objetivos específicos: identificar se há benefícios da vivência da dança para pessoas diagnosticadas com TEA e suscitar se o ensino da dança para pessoas com TEA afeta a vida das professoras. Seguindo a abordagem qualitativa, os dados foram coletados através de entrevistas com um roteiro de perguntas semiestruturadas, dirigidas a profissionais que atuaram no ensino de dança para pessoas com TEA. Diante da análise das respostas, identificamos três categorias temáticas: Prática vs. Teoria; O indivíduo como ser único e O impacto da prática. Foi possível identificar que as experiências com esse público são muito singulares, visto que cada profissional possui uma vivência diferente devido às especificidades de seus alunos; existe a necessidade de compreender o aluno como um indivíduo único e singular e respeitar suas especificidades; houve melhora na comunicação, diminuição de movimentos estereotipados, melhora do afeto e demonstração dele, da socialização e do desempenho motor. Concluiu-se com a pesquisa que a dança possibilita benefícios em diversas esferas do Transtorno do Espectro Autista, confirmando a eficiência dessa intervenção na vida do indivíduo, mas, além disso, reforçando a importância de uma relação professor/aluno bem construída, baseada em respeito, escuta e cuidado, para que haja espaço para esses benefícios se desenvolverem no tempo devido e da maneira correta.
Dance in the development of people with autism spectrum disorder
Keywords: Autism spectrum disorders; Dance; Physical education; Transtorno do Espectro Autista; Dança; Formação; Educação física